Purinergic signalling in graft-versus-host disease. (February 2023) - Sluyter, Ronald; Cuthbertson, Peter; Elhage, Amal; Sligar, Chloe; Watson, Debbie
Abstract: Allogeneic hematopoietic stem cell transplantation is used to treat blood cancers, but often results in lethal graft-versus-host disease (GVHD). GVHD is an inflammatory disorder mediated by donor leukocytes that damage host tissues. Purinergic signalling plays important roles in GVHD development in mice but studies of these pathways in human GVHD remain limited. P2X7 receptor activation by ATP on host antigen presenting cells contributes to the induction of GVHD, while activation of this receptor on regulatory T cells, myeloid-derived suppressor cells and possibly type 3 innate lymphoid cells results in their loss to promote GVHD progression. In contrast, A2A receptor activation by adenosine on donor T cells serves to restrict GVHD development. These and other purinergic signalling molecules remain potential biomarkers and therapeutic targets in GVHD.